The creative thinking process of teachers in designing mathematical tasks - Taufiq Taufiq; M T Budiarto; T Y E Siswono (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Students have different backgrounds and abilities. Because of that, teachers must be smart in choosing and giving math tasks to their students. The aim of this study is to reveal the process of creative thinking of teachers in designing mathematical tasks. A participant in this study was Bibah (it is a fake name) based on the functional position of the teacher (focusing on the baginner teacher) elementary school teachers in the Pangkep district of South Sulawesi. This study uses a qualitative approach, with data collection methods using task-based interviews. From the results obtained, we find the biblical thinking process following the sequence of the synthesis stage of ideas, building ideas, planning the implementation of ideas, synthesizing ideas, planning the implementation of ideas and application of ideas.Students have different backgrounds and abilities. Because of that, teachers must be smart in choosing and giving math tasks to their students. The aim of this study is to reveal the process of creative thinking of teachers in designing mathematical tasks. A participant in this study was Bibah (it is a fake name) based on the functional position of the teacher (focusing on the baginner teacher) elementary school teachers in the Pangkep district of South Sulawesi. This study uses a qualitative approach, with data collection methods using task-based interviews. From the results obtained, we find the biblical thinking process following the sequence of the synthesis stage of ideas, building ideas, planning the implementation of ideas, synthesizing ideas, planning the implementation of ideas and application of ideas.